STRATEGI PENGGUNAAN KOSAKATA DAN TATA BAHASA DALAM BERITA HARIAN UMUM INDEPENDEN SINGGALANG - Dina Ramadhanti (Universitas PGRI Sumatera Barat, 2015)
This article aims to describe the strategy of the use of vocabulary and grammer in general daily news i Singgalang newspaper. The method used is descriptive method to descripe the use of vocabulary and grammer in writing news writer. The discusiion carried out in accordance with the opinion expressed by Roger Flower, etal. Vocabulary and grammer in general daily news in singgalang newspaper tend to marginalize the victim because writers to write descriptions of the perpetrator, while the victim semed to be ignored. Vocabulary used tend vocabulary and grammer marginalizations tend syntax used passive or passivation and nominalition resulting in the removal of the perpetrator in the news. Victims tend to be the main core of the problem